2020
DOI: 10.1021/acsnano.0c04640
|View full text |Cite
|
Sign up to set email alerts
|

Toward Brain-on-a-Chip: Human Induced Pluripotent Stem Cell-Derived Guided Neuronal Networks in Tailor-Made 3D Nanoprinted Microscaffolds

Abstract: Brain-on-a-chip (BoC) concepts should consider three-dimensional (3D) scaffolds to mimic the 3D nature of the human brain not accessible by conventional planar cell culturing. Furthermore, the essential key to adequately address drug development for human pathophysiological diseases of the nervous system, such as Parkinson’s or Alzheimer’s, is to employ human induced pluripotent stem cell (iPSC)-derived neurons instead of neurons from animal models. To address both issues, we present electrophysiologically mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 90 publications
5
54
0
Order By: Relevance
“…[16][17][18][19] The influence of the substrate in terms of chemical and topological properties has been tested, for example, for adhesion, proliferation, viability, migration, and guidance of seeded cells. [20][21][22][23][24][25][26] In this context, a particular subset of substrates featuring upright arranged high aspect ratio nanostructures-so-called nanowire (NW) arraysplay an increasingly important role. [27][28][29][30][31][32][33] Nanowire arrays can affect biological parameters such as cellular growth, viability, morphology, and mechanotransduction machinery, [34][35][36][37][38][39] while electrophysiological parameters are maintained.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] The influence of the substrate in terms of chemical and topological properties has been tested, for example, for adhesion, proliferation, viability, migration, and guidance of seeded cells. [20][21][22][23][24][25][26] In this context, a particular subset of substrates featuring upright arranged high aspect ratio nanostructures-so-called nanowire (NW) arraysplay an increasingly important role. [27][28][29][30][31][32][33] Nanowire arrays can affect biological parameters such as cellular growth, viability, morphology, and mechanotransduction machinery, [34][35][36][37][38][39] while electrophysiological parameters are maintained.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as damage/loss of endothelial glycocalyx contributes to additional brain damage during reperfusion; perhaps artificial glycocalyx could be transplanted to ameliorate this in the future [ 106 ]. Additionally, in vitro disease modeling, such as brain/body-on-a-chip methods, is also useful, especially in determining the effect of cytokines and the efficacy of conditioned media [ 47 , 109 ]. IPSCs are particularly useful for this purpose, given their endless proliferative abilities and their ability to tailor disease modeling to any patient [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in vitro disease modeling, such as brain/body-on-a-chip methods, is also useful, especially in determining the effect of cytokines and the efficacy of conditioned media [ 47 , 109 ]. IPSCs are particularly useful for this purpose, given their endless proliferative abilities and their ability to tailor disease modeling to any patient [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through these features, OOCs provide improved consistency of tissue structure and phenotypes for studies of organ-level functions, while often incorporating only a few cell types found in the native organ. Examples of OOCs include heart muscle (Mathur et al, 2015;Ronaldson-Bouchard et al, 2018;Zhao et al, 2019;Tiburcy, 2017), liver ((Kostrzewski et al, 2019;Schepers et al, 2016) alveolar unit of the lung (Huh et al, 2010), brain (Harberts et al, 2020) and blood-brain barrier (Vatine et al, 2019), kidney glomerulus and proximal tubule (Zhou et al, 2016;Homan et al, 2016), neuromuscular junction (Afshar Bakooshli et al, 2019), vascular network (Zhang et al, 2016), skin (Abaci et al, 2018), retina (Achberger et al, 2019), pancreas (Bauer et al, 2017), gut (Kim et al, 2016), bone marrow (Chou et al, 2020) placenta (Blundell et al, 2016), and tumors (Lai et al, 2020), all of which are being used to study tissue maturation, regeneration, and disease.…”
Section: Introductionmentioning
confidence: 99%